2018
DOI: 10.1016/j.bjorl.2017.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Short-term evaluation of tegumentary changes of the nose in oral breathers undergoing rapid maxillary expansion

Abstract: In short-term, rapid maxillary expansion provided a statistically significant increase in the dimensions of the soft tissues of the nose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 20 publications
1
5
0
9
Order By: Relevance
“…Another potential side effect after RME could be the development of a dorsal hump, 5,17,18 which was not found in the patients in this study. The short-term nasal hard tissue change showed a significant increase in pyriform height and width, which was consistent with Badreddine et al, 10,11 Cordasco et al, 19 Palaisa et al, 20 and Fastuca et al 21 For the long term, this study examined how RME affected patients' nasal growth in comparison with the nontreatment CG. The differences between T1 and T3 values in the TG (D T1-T3, average 2.84 years) was compared with the differences between T1 0 and T3 0 in the CG (DT1 0 -T3 0 , average 2.25 years).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Another potential side effect after RME could be the development of a dorsal hump, 5,17,18 which was not found in the patients in this study. The short-term nasal hard tissue change showed a significant increase in pyriform height and width, which was consistent with Badreddine et al, 10,11 Cordasco et al, 19 Palaisa et al, 20 and Fastuca et al 21 For the long term, this study examined how RME affected patients' nasal growth in comparison with the nontreatment CG. The differences between T1 and T3 values in the TG (D T1-T3, average 2.84 years) was compared with the differences between T1 0 and T3 0 in the CG (DT1 0 -T3 0 , average 2.25 years).…”
Section: Discussionsupporting
confidence: 85%
“…Baysal et al 13 reported that alar base width was greater by approximately 1 mm in the RME treatment group after a 6month retention period. Badreddine et al 11 reported that, after RME, the alar base width, alar width, and height of the nasal soft tissues increased, whereas changes did not occur in the control group. Berger et al 5 reported a 2-mm increase in alar width, which was maintained 1 year after tooth-borne expansion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, in recent years, the effect of RPE on nasal soft tissue changes has been investigated with CBCT. [8][9][10] However, only the short-term effects of expansion on the nasal cavity were observed in these studies, and long-term changes have not been investigated. 9,10 In addition, in some studies, the changes in the nasal cavity with expansion were not compared with controls.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] However, only the short-term effects of expansion on the nasal cavity were observed in these studies, and long-term changes have not been investigated. 9,10 In addition, in some studies, the changes in the nasal cavity with expansion were not compared with controls. 8,7 Even though a recent study investigated the long-term effects of conventional RPE on the nasal cavity, the effects of MARPE were not investigated.…”
Section: Introductionmentioning
confidence: 99%